Inhibition of Circulating Exosomal miRNA-20b-5p Accelerates Diabetic Wound Repair - Chen K (Dove Medical Press, 2021)
Kai Chen, Tao Yu, Xin Wang Department of Orthopedic Surgery, Tongji Hospital, Tongji University School of Medicine, Shanghai 200065, People’s Republic of ChinaCorrespondence: Xin Wang; Tao YuDepartment of Orthopedic Surgery, Tongji Hospital, Tongji University School of Medicine, Shanghai 200065, People’s Republic of ChinaTel/Fax +86 21 8572 6525Email 00848@tongji.edu.cn; yutao247@tongji.edu.cnPurpose: Efficient approaches to reliably improving wound healing in diabetic patients remain to be developed. Exosomes are nanomaterials from which therapeutically active microRNAs (miRNAs) can be isolated. In the present report, we therefore isolated circulating exosome-derived miRNAs from patients with diabetes and assessed the impact of these molecules on wound healing.Patients and Methods: Exosomes were isolated from the serum of control or diabetic patients (Con-Exos and Dia-Exos, respectively), after which the effects of these exosomes on cellular activity and wound healing were assessed.Results: We determined that miR-20b-5p was overexpressed in Dia-Exos and that it functioned by impairing wound repair by suppressing vascular endothelial growth factor A (VEGFA) expression. Consistent with such a model, the administration of Dia-Exos or this miRNA both in vivo and in vitro was sufficient to slow wound repair.Conclusion: Dia-Exos exhibit significant increases in miR-20b-5p relative to Con-Exos, and this miRNA can be transferred into HSFs wherein it can suppress VEGFA expression and thereby slow the process of wound healing.Keywords: nanomedicine, exosome, miRNA, diabetes, wound, fibroblast